Complementary therapy in pregnancy: Indonesian Pregnant women’s Insight - Ady Irawan; Anggie Pradana Putri (LPPM Universitas Duta Bangsa Surakarta, 2022)
Background: Complementary therapies are treatments not typically prescribed by physicians as part of integrated medical care. Pregnant women are suggested to benefit from complementary therapy because it carries fewer risks than conventional therapy and they have a high degree of control over their health. Aim: This study aims to explore pregnant women’s insight into complementary therapy. Method: This study employed mix method to describe pregnant women’s insight into complementary therapy. Result: More than 50% of pregnant women in Indonesia have a good perception of complementary therapy. Three themes, including 1) definition of complementary therapy, 2) positive perception of complementary therapy, 3) negative perceptions of complementary therapy; supported the insight on complementary therapy in pregnancy. Conclusion: This study demonstrates that pregnant women in Indonesia have a positive perception of complementary therapies. However, health promotion connected to complementary therapy is required as a supplement to conventional therapy. Keywords: complementary therapy, pregnancy, pregnant women, perception